The Role of Sufism Among Turkey’s Secularism Policies - Ghafur, Muhammad Fakhry; Mashad, Dhurorudin; Basyar, M. Hamdan (Proceedings of International Conference on Muslim Society and Thought, 2024)
This paper examines the case of religious political movements and the development of Sufism in a Muslim country, with a focus on Turkiye, a country where secularism is strictly enforced. Since 1924, the Muslim-majority country has established itself as a secular state, which separates religion from state politics. The policy initiated by Kemal Atatürk represented a rejection of the Islamic caliphate system that had been implemented by the Uthmaniyah dynasty since the 13th century. Ataturk sought to modernize Turkiye based on democratic and secular principles. Although secularism has been a long-standing feature of Turkish society, the influence of Islam remains evident in the socio-cultural fabric of the country. Indeed, the passion for Islam has been visible in the political landscape since the early 1990s, particularly in sufism movement and political party. This paper is based on a qualitative study conducted through a literature search, supported by observation of events based on information from the mass media. The result of this study is an important finding about the reality of political religion and the Sufism movement in the implementation of secularism in the Muslim country of Turkiye. This insight reveals a paradox between the politics of religion and secularism in the Turkiye state.